Use of Structural Equation Modeling Method for Analysis of Factors Affecting the Quality of Library Services of Bhayangkara University - Andrew Aldy Wala; Syariful Alim; Fardanto Setyatama (Fakultas Teknik Universitas Bhayangkara, 2020)
One of the common problems often faced by companies or organizations in the service sector is the problem of service user dissatisfaction with the quality of service provided. One of the service units in Ubhara is the Bhayangkara University Library. The quality of library services can be influenced by several factors, such as library collections, employee competence and library facilities. The data collection technique used a Likert scale questionnaire, which consists of 3 exogenous latent variables and 1 endogenous latent variable with a total of 14 indicators. The method used is data analysis using the Structural Equation Modeling (SEM) approach assisted by the LISREL 8.80 program. The problem in this study is to determine the effect and significance of the library collection variables (X1), employee competence (X2) and library facilities (X3) on service quality (Y). The hypothesis in this study is that there is a positive influence between employee competence and library facilities on service quality. The number of samples in this study were 100 students who visited the Ubhara Library. Based on the results of the study, the variable X1 estimate is 0.09 and the T-value is 0.67, the variable X2 estimate is 0.44 and the T-value is 2.97 and the variable X3 estimate is 0.46 and the T-value is 3.02. So the latent variables of employee competence and library facilities have a positive effect on the quality of library services. Meanwhile, the library collection variable has no positive effect on service quality.